STUDY OF ETIOLOGICAL, CLINICAL PROFILE AND CORRELATION OF BISAP SCORING IN ASSESSING SEVERITY AND OUTCOME OF PATIENTS DIAGNOSED WITH ACUTE PANCREATITIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute pancreatitis (AP) is defined as inflammatory process due to auto-digestion of the gland by pancreatic digestive enzymes, leading to impairment of function or any morphologic changes. Objective: The study provides comprehensive insights into the demographic, clinical, and biochemical characteristics of acute pancreatitis patients. Methods: This Prospective observational study was conducted among patients attending OPD and IPD of General Medicine department of KBN Teaching & General Hospital Kalaburagi. Period of Study was 18 months (1st march 2023 to 30th September 2024). Result: The study highlights the diverse presentations and severity of acute pancreatitis, emphasizing the prognostic value of BISAP and CT severity scores. While gender was not a determining factor in disease severity, age and specific biochemical markers significantly influenced patient outcomes. These findings underscore the need for early detection and targeted management strategies to improve prognosis. Conclusion: The study identified BISAP as reliable predictor of disease prognosis. Higher BISAP score is strongly associated with increased mortality (P